Eastward Jet Lag is Associated with Impaired Performance and Game Outcome in the National Basketball Association - Leota, Josh; Hoffman, Daniel; Czeisler, Mark É.; Mascaro, Luis; Drummond, Sean P.A.; Anderson, Clare; Rajaratnam, Shantha M.W.; Facer-Childs, Elise R. (Frontiers in Physiology, 2022)
Objectives: Elite athletes are often required to travel across time zones for national and international competitions, causing frequent jet lag. The aim of this study was to examine whether the direction of travel-related jet lag is associated with performance in the National Basketball Association (NBA), and if so, to explore potential mechanisms. Methods: Ten seasons comprising of 11,481 games of NBA data from the 2011/2012 to the 2020/2021 regular season were analyzed using multi-level mixed models with one fixed factor (three levels; jet lag direction: eastward vs. westward vs. no jet lag) and three random factors (team, opponent, game time). Predicted circadian resynchronization rate was accounted for, and home and away games were analysed separately. Mediation analyses were performed to examine potential mechanisms. Results: Among home teams, eastward (but not westward) jet lag was associated with reduced winning (Δ (i.e., change) = -6.03%, p = .051, marginal), points differential (Δ = -1.29 points, p = .015), rebound differential (Δ = -1.29 rebounds, p < .0001), and effective field goal percentage differential (Δ = -1.2%, p < .01). As the magnitude of eastward jet lag increased, home team points differential decreased (2 hr Δ = -4.53 points, p < .05; 1 hr Δ = -0.72 points, p = .07). No significant associations were found between jet lag and away team performance. Conclusion: Eastward jet lag was associated with impaired performance for home (but not away) teams. Sleep and circadian disruption associated with advancing phase following eastward travel may have significant adverse consequences on performance in the NBA, particularly when recovery time is limited. Sports organisations could consider chronobiology-informed scheduling and interventions to maximise recovery and performance of their athletes.